It’s not All Doom and Gloom: Prune Belly Syndrome Associated with VACTERL - Awad, Karim; Lall, Anupam (Journal of Neonatal Surgery, 2016)
Prune belly syndrome is a rare abnormality; its association with VACTERL is even rarer. This association has been reported in literature a few times since first reported in 1993 and so far the majority have either been stillbirths or died shortly after birth. We present a case of Prune belly syndrome associated with VACTERL who is now one year old.